The impact of brand associations on brand loyalty in the football industry A comparison of fans from developed and emerging football markets - Maderer, Daniel; Holtbrügge, Dirk; Woodland, Rachel (Sport, Business and Management, 2016)
Purpose - The purpose of this paper is to explore the impact of brand associations on brand loyalty of fans toward professional football clubs in developed and emerging football markets (EFM). In particular, the following research questions are answered: how important are different determinants of brand associations for fans from developed football markets (DFM) and EFM? Are there any major differences in the importance of different brand associations and their influence on brand loyalty between fans from DFM and EFM?
Created from Fastlane, WoS look-up